Charging roll for electrophotographic equipment and method for producing the charging roll for electrophotographic equipment

The electrophotographic charging roll with a surface layer containing specific polymers and dispersants addresses the compatibility issues between fluororesin and carbon black, achieving excellent charging and uniform charging properties by enhancing carbon black dispersibility.

JP7655835B2Active Publication Date: 2025-04-02SUMITOMO RIKO CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2021177940
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-04-02
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The use of fluororesin as a surface binder in electrophotographic charging rolls is not compatible with carbon black, leading to deteriorated dispersibility and uneven discharge, which impairs uniform charging properties.

Method used

A charging roll with a surface layer containing specific polymers (fluoropolymers or silicone polymers), carbon black, ester-type polyurethane-based polymer dispersants, polyethyleneimine-based polymer dispersants, and polyamine-based polymer dispersants with a polyester structure, which improves the dispersibility and uniformity of carbon black.

Benefits of technology

The solution achieves excellent charging and uniform charging properties by enhancing the dispersibility of carbon black and improving the compatibility with low dielectric constant binders, resulting in improved capacitance and reduced resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655835000002
    Figure 0007655835000002
  • Figure 0007655835000001
    Figure 0007655835000001
Patent Text Reader

Abstract

To provide a charging roll for electrophotographic apparatuses that excels in chargeability and uniform charging property, and a method for manufacturing the charging roll for electrophotographic apparatuses.SOLUTION: Provided is a charging roll 10 for electrophotographic apparatuses comprising a shaft body 12, an elastic substance layer 14 which is formed on the outer circumferential surface of the shaft body 12, and a surface layer 16 which is formed on the outer circumferential surface of the elastic substance layer 14, the surface layer 16 containing the following (A) to (D). (A) One or more polymers selected from a fluorine polymer and a silicone polymer having a dielectric constant of 2.2 to 2.5 inclusive; (B) carbon black; (C) one or more macromolecular dispersants selected from an ester type polyurethane macromolecular dispersant and a polyethyleneimine macromolecular dispersant having a carboxyl group; (D) polyamine macromolecular dispersant having a polyester structure in a side chain.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a charging roll for electrophotographic equipment that is suitably used in electrophotographic equipment such as copying machines, printers, and facsimiles that employ an electrophotographic system, and to a method for manufacturing the charging roll for electrophotographic equipment. [Background technology]

[0002] In electrostatic charge rolls for electrophotographic devices, carbon black is sometimes blended into the surface layer to improve the amount of charge, and fluororesin is sometimes used as a binder for the surface layer (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-268613 Summary of the Invention [Problem to be solved by the invention]

[0004] If a fluororesin is used as a binder for the surface layer, it is incompatible with carbon black, which deteriorates the dispersibility of the carbon black and causes non-uniform discharge, which impairs uniform charging.

[0005] An object of the present invention is to provide a charging roll for electrophotographic equipment, which is excellent in charging properties and uniform charging, and a method for producing the charging roll for electrophotographic equipment. [Means for solving the problem]

[0006] The charging roll for an electrophotographic device according to the present invention comprises a shaft, an elastic layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastic layer, and the surface layer contains the following (A) to (D): (A) one or more polymers selected from fluoropolymers and silicone polymers having a dielectric constant of 2.2 or more and 2.5 or less; (B) Carbon black (C) one or more polymer dispersants having a carboxyl group selected from ester-type polyurethane polymer dispersants and polyethyleneimine polymer dispersants (D) Polyamine-based polymer dispersant having a polyester structure in the side chain

[0007] The DBP absorption amount of (B) is 115 cm 3 / 100g or more 160cm 3 / 100g or less, and the specific surface area of ​​(B) is 25m 2 / g or more 75m 2 / g or less, and the average particle size of (B) is preferably 35 nm or more and 75 nm or less. The surface layer contains roughness-forming particles that form surface roughness, and the roughness-forming particles preferably have either a carbonyl group or a hydroxyl group, or both. The content of (D) relative to (B) is preferably 1.5 to 3.0 in mass ratio. The content of (C) relative to (B) is preferably 1.5 to 3.0 in mass ratio. The polyester terminal of (D) is preferably a ring. The main chain of (C) is preferably a polyalkylene oxide structure. The carboxyl group of (C) is preferably a carboxylate group having a quaternary amine structure.

[0008] In the method for producing a charging roll for an electrophotographic device according to the present invention, the surface layer is formed from a surface layer composition containing the above-mentioned (A) to (D), and the surface layer composition is formed by mixing the above-mentioned (B) and the above-mentioned (D), followed by mixing the above-mentioned (C), and then mixing the above-mentioned (A). Effect of the Invention

[0009] The electrostatic charge roll for electrophotographic equipment according to the present invention comprises a shaft, an elastic layer formed on the outer peripheral surface of the shaft, and a surface layer formed on the outer peripheral surface of the elastic layer, and since the surface layer contains the above-mentioned (A) to (D), it has excellent electrostatic charge properties and uniform electrostatic charge properties.

[0010] The DBP absorption of (B) is 115 cm 3 / 100g or more 160cm 3 / 100g or less, and the specific surface area of ​​(B) is 25m 2 / g or more 75m 2 / g or less and the average particle size of (B) is 35 nm or more and 75 nm or less, (B) can exhibit low resistance and high capacitance, thereby improving the chargeability.

[0011] When the surface layer contains roughness-forming particles that form surface roughness and the roughness-forming particles have either or both of a carbonyl group and a hydroxyl group, the roughness-forming particles are composed of a material with a high dielectric constant, thereby improving electrostatic chargeability.

[0012] When the content of (D) relative to (B) is 1.5 or more and 3.0 or less in mass ratio, the dispersion effect of (D) due to the steric hindrance of (B) is excellent, and the uniform charging property is improved.

[0013] When the content of (D) relative to (C) is 1.5 or more and 3.0 or less in mass ratio, the dispersion effect of (C) due to electrostatic repulsion of (B) is excellent, and the uniform charging property is improved.

[0014] When the polyester (D) has a cyclic end, the dispersion effect due to steric hindrance can be further improved.

[0015] When the (C) has a polyalkylene oxide structure in its main chain, the electrostatic repulsion of the (C) is enhanced, the dispersion effect of the (B) due to the electrostatic repulsion of the (C) is improved, and the uniform charging property is improved.

[0016] When the carboxyl group of (C) is a carboxylate salt group having a quaternary amine structure, the steric hindrance of (C) is enhanced, the dispersion effect of (B) due to the steric hindrance of (C) is improved, and the uniform charging property is improved.

[0017] According to the method for producing a charging roll for an electrophotographic device of the present invention, the surface layer is formed from a surface layer composition containing the (A) to (D), and the surface layer composition is formed by mixing the (B) and the (D), followed by mixing the (C), and then mixing the (A), so that a charging roll for an electrophotographic device having excellent charging properties and uniform charging properties can be provided. [Brief description of the drawings]

[0018] [Figure 1] 1A is a schematic external view of a charging roll for an electrophotographic device according to one embodiment of the present invention, and FIG. 1B is a cross-sectional view taken along line AA thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The charging roll for electrophotographic equipment according to the present invention (hereinafter, simply referred to as the charging roll) will be described in detail. Fig. 1 is a schematic external view (a) of the charging roll for electrophotographic equipment according to one embodiment of the present invention, and its AA line cross-sectional view (b).

[0020] The electrostatic charge roll 10 includes a shaft 12, an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastic layer 14. The elastic layer 14 is a layer (base layer) that serves as the base of the electrostatic charge roll 10. The surface layer 16 is a layer that appears on the surface of the electrostatic charge roll 10.

[0021] The shaft body 12 is not particularly limited as long as it is conductive. Specific examples include a core bar made of a solid or hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, primer, or the like may be applied to the surface of the shaft body 12 as needed. In other words, the elastic layer 14 may be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, primer, or the like may be made conductive as needed.

[0022] The elastic layer 14 contains a crosslinked rubber. The elastic layer 14 is formed of a conductive rubber composition containing an uncrosslinked rubber. The crosslinked rubber is obtained by crosslinking the uncrosslinked rubber. The uncrosslinked rubber may be a polar rubber or a non-polar rubber.

[0023] The polar rubber is a rubber having a polar group, and examples of the polar group include a chloro group, a nitrile group, a carboxyl group, and an epoxy group. Specific examples of the polar rubber include hydrin rubber, nitrile rubber (NBR), urethane rubber (U), acrylic rubber (a copolymer of an acrylic acid ester and 2-chloroethyl vinyl ether, ACM), chloroprene rubber (CR), and epoxidized natural rubber (ENR). Among the polar rubbers, hydrin rubber and nitrile rubber (NBR) are more preferable from the viewpoint that the volume resistivity is particularly likely to be low.

[0024] Examples of the hydrin rubber include epichlorohydrin homopolymer (CO), epichlorohydrin-ethylene oxide binary copolymer (ECO), epichlorohydrin-allyl glycidyl ether binary copolymer (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymer (GECO).

[0025] The urethane rubber may be a polyether type urethane rubber having an ether bond in the molecule. The polyether type urethane rubber may be produced by reacting a polyether having hydroxyl groups at both ends with a diisocyanate. The polyether may be, but is not limited to, polyethylene glycol, polypropylene glycol, etc. The diisocyanate may be, but is not limited to, tolylene diisocyanate, diphenylmethane diisocyanate, etc.

[0026] Non-polar rubbers include silicone rubber (Q), isoprene rubber (IR), natural rubber (NR), styrene butadiene rubber (SBR), butadiene rubber (BR), and the like.

[0027] Examples of the crosslinking agent include a sulfur crosslinking agent, a peroxide crosslinking agent, and a dechlorination crosslinking agent. These crosslinking agents may be used alone or in combination of two or more.

[0028] Examples of the sulfur crosslinking agent include conventionally known sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymeric polysulfides.

[0029] Examples of the peroxide crosslinking agent include conventionally known peroxide crosslinking agents such as peroxyketals, dialkyl peroxides, peroxyesters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.

[0030] Examples of the dechlorinating crosslinking agent include dithiocarbonate compounds, more specifically, quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, 5,8-dimethylquinoxaline-2,3-dithiocarbonate, etc.

[0031] The amount of the crosslinking agent to be blended is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and even more preferably within a range of 0.5 to 1.5 parts by mass, per 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0032] When a dechlorination crosslinking agent is used as a crosslinking agent, a dechlorination crosslinking accelerator may be used in combination. Examples of the dechlorination crosslinking accelerator include 1,8-diazabicyclo(5,4,0)undecene-7 (hereinafter abbreviated as DBU) or a weak acid salt thereof. The dechlorination crosslinking accelerator may be used in the form of DBU, but in terms of handling, it is preferable to use it in the form of a weak acid salt thereof. Examples of the weak acid salt of DBU include carbonate, stearate, 2-ethylhexyl acid salt, benzoate, salicylate, 3-hydroxy-2-naphthoate, phenol resin salt, 2-mercaptobenzothiazole salt, and 2-mercaptobenzimidazole salt.

[0033] The content of the dechlorination crosslinking accelerator is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and further preferably within a range of 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.

[0034] A conductive agent can be blended into the elastic layer 14 to impart electrical conductivity. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive agent include carbon black, graphite, and conductive metal oxides. Examples of the conductive metal oxide include conductive titanium oxide, conductive zinc oxide, and conductive tin oxide. Examples of the ionic conductive agent include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the elastic layer 14 as necessary. Examples of the additives include lubricants, vulcanization accelerators, antiaging agents, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, foaming agents, fillers, dispersants, defoamers, pigments, and mold release agents.

[0035] The elastic layer 14 can be adjusted to a desired volume resistivity by adjusting the type of crosslinked rubber, the amount of ionic conductive agent, the amount of electronic conductive agent, etc. 2 ~10 10 Ω cm, 10 3 ~10 9 Ω cm, 104 ~10 8 The range may be set appropriately, for example to Ω·cm.

[0036] The thickness of the elastic layer 14 is not particularly limited, and may be appropriately set within a range of 0.1 to 10 mm depending on the application.

[0037] The surface layer 16 contains the following (A) to (D). (A) one or more polymers selected from fluoropolymers and silicone polymers having a dielectric constant of 2.2 or more and 2.5 or less; (B) Carbon black (C) one or more polymer dispersants having a carboxyl group selected from ester-type polyurethane polymer dispersants and polyethyleneimine polymer dispersants (D) Polyamine-based polymer dispersant having a polyester structure in the side chain

[0038] (A) is one or more polymers selected from fluoropolymers and silicone polymers. In this way, since (A) is a material with low dielectric constant and low abrasion, it is possible to suppress contamination of toner and toner additives. On the other hand, if (A) has a low dielectric constant, it has poor compatibility with (B) carbon black, and the dispersibility of (B) carbon black decreases. This reduces the uniform charging property. For this reason, in the present invention, the above-mentioned two types of dispersants (C) and (D) with different properties are used in combination. This makes it possible to increase the dispersibility of (B) carbon black and achieve excellent uniform charging property even when a binder with a low dielectric constant such as (A) is used.

[0039] In (A), the fluoropolymer is a polymer containing a fluorine group. Examples of the fluoropolymer include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), ethylenetetrafluoroethylene copolymer (ETFE), and polyvinylidene fluoride (PVDF). The silicone polymer may be one generally known as organopolysiloxane. The silicone polymer may have a modified group. Examples of the modified silicone polymer include phenyl-modified silicone, ether-modified silicone, and ester-modified silicone.

[0040] The one or more polymers selected from fluoropolymers and silicone polymers (A) have a dielectric constant of 2.2 or more and 2.5 or less. In this way, since (A) is a material with low dielectric constant and low wear, it is possible to suppress contamination of toner and toner external additives. Furthermore, since the dielectric constant of (A) is within the above range, the charging roll 10 can exhibit excellent charging properties. If the dielectric constant of (A) is less than 2.2, the electrostatic capacitance of (A) becomes small and charging properties become poor. From this viewpoint, the dielectric constant of (A) is preferably 2.3 or more. On the other hand, if the dielectric constant of (A) is more than 2.5, the dipole moment of (A) increases, and the dispersants of (C) and (D) tend to adhere to (A), the interaction between (C) and (D) and (B) becomes small, and the dispersibility of (B) carbon black decreases. Furthermore, if the dielectric constant of (A) is more than 2.5, the charging properties become more environmentally dependent and the environmental dependency becomes poor. From this viewpoint, the relative dielectric constant of (A) is preferably 2.4 or less.

[0041] (B) carbon black contributes to improving electrostatic chargeability. From the viewpoint of improving electrostatic chargeability, it is preferable that (B) carbon black has a DBP absorption amount, a specific surface area, and an average particle size within a predetermined range in order to exhibit low resistance and high capacitance.

[0042] (B) The DBP absorption amount of carbon black is preferably 115 cm 3 / 100g or more, preferably 120cm 3 / 100g or more, more preferably 130cm 3 On the other hand, the DBP absorption amount of the carbon black (B) is preferably 160 cm 3 / 100g or less, more preferably 150cm 3 / 100g or less, more preferably 140cm 3 The DBP absorption amount of carbon black is calculated based on the amount of DBP (dibutyl phthalate) absorbed by 100 g of carbon black in accordance with JIS K6221.

[0043] From the viewpoint of improving the electrostatic capacity, it is preferable that the carbon black (B) has a relatively small specific surface area and a large particle size. Specifically, the carbon black (B) has a specific surface area of ​​preferably 75 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 60m 2 / g or less. The average particle size is preferably 35 nm or more, more preferably 40 nm or more. On the other hand, from the viewpoint of low resistance, the specific surface area of ​​(B) carbon black is preferably 25 m 2 / g or more, more preferably 30m 2 / g or more. The average particle size is preferably 75 nm or less, more preferably 70 nm or less, and even more preferably 60 nm or less. The specific surface area of ​​carbon black is a value measured by the BET method. The average particle size of carbon black is represented by the arithmetic mean diameter obtained by observing carbon black under an electron microscope.

[0044] From the viewpoint of easily ensuring capacitance, the content of (B) carbon black is preferably 5 parts by mass or more per 100 parts by mass of (A). More preferably, it is 10 parts by mass or more, and even more preferably, it is 20 parts by mass or more. Moreover, from the viewpoint of easily suppressing insufficient discharge, the content of (B) carbon black is preferably 75 parts by mass or less per 100 parts by mass of (A). More preferably, it is 70 parts by mass or less, and even more preferably, it is 60 parts by mass or less. And, when the content of (B) carbon black is 5 parts by mass or more and 75 parts by mass or less per 100 parts by mass of (A), it is easy to maintain the resistance and capacitance within a suitable range.

[0045] (C) and (D) are used in combination to improve the dispersibility of (B) carbon black in (A) with a low dielectric constant. Using only (C) or (D) alone does not provide sufficient dispersibility of (B) in (A), making it impossible to achieve uniform charging.

[0046] (C) is a dispersant having a carboxyl group. The carboxyl group includes both carboxylic acid (-COOH) and carboxylate (-COOM). M represents a metal having a valence of one or more or a quaternary amine. (C) is adsorbed to the surface of (B) carbon black, and by having a carboxyl group, it suppresses aggregation of the particles of (B) carbon black due to electrical repulsion, thereby improving the dispersibility of (B) carbon black. As the carboxyl group, a carboxylate salt group having a quaternary amine structure is particularly preferable. The steric hindrance of (C) is increased, and the dispersion effect of the steric hindrance of (B) by (C) is improved, improving the uniform charging property.

[0047] (C) is a polymer dispersant composed of a polymer. Because it has a larger molecular weight than low-molecular dispersants such as fatty acids and fatty acid salts, it is expected to have a dispersing effect on (B) carbon black by utilizing steric hindrance. Examples of the polymer dispersant (C) include ester-type polyurethane polymer dispersants and polyethyleneimine polymer dispersants. These may be included alone as (C), or two or more types may be combined.

[0048] Ester-type polyurethane polymer dispersants tend to have a large electrostatic repulsion effect due to the large dipole moment of the ester-type urethane group (-NH-COO-). Also, polyethyleneimine polymer dispersants tend to have a large electrostatic repulsion effect due to the large dipole moment of the imine group and the large number of NH groups in the polyethyleneimine.

[0049] Ester type polyurethane has an ester bond in the molecule. Ester type polyurethane contains polyester polyol as a polyol component. Examples of polyester polyol include polyethylene adipate, polybutylene adipate, polyhexylene adipate, copolymers of ethylene adipate and butylene adipate, carbonate diol, etc. Examples of the isocyanate component of polyurethane include, but are not limited to, tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), etc.

[0050] (C) may have a polyalkylene oxide structure in the main chain. When the main chain has a polyalkylene oxide structure, electrostatic repulsion is enhanced. Examples of the polyalkylene oxide structure include a polyethylene oxide structure and a polypropylene oxide structure.

[0051] Examples of ester-type polyurethane polymer dispersants having a carboxyl group include Lubrizol's Solsperse 75500, 76500, 82500, and 83500. Examples of polyethyleneimine polymer dispersants having a carboxyl group include Lubrizol's Solsperse 32500.

[0052] The content of (C) is preferably 1.5 or more and 3.0 or less in mass ratio to (B). When the content is 3.0 or less, aggregation of (C) is suppressed, and a decrease in electrostatic chargeability is suppressed. From this viewpoint, the content is more preferably 2.5 or less. On the other hand, when the content is 1.5 or more, the dispersing effect of (B) due to electrostatic repulsion of (C) can be increased. From this viewpoint, the content is more preferably 2.0 or more.

[0053] (D) is a polyamine-based polymer dispersant. The amino groups at the ends of the polyamine molecular chains have good affinity with the carboxyl and hydroxyl groups on the carbon black surface, allowing them to preferentially adsorb to the carbon black surface. (D) is a polyamine-based polymer dispersant (a polymer dispersant composed of polymers), which prevents the particles of (B) carbon black from agglomerating together due to steric hindrance, thereby improving the dispersibility of (B) carbon black.

[0054] (D) has a polyester structure in the side chain. This can further improve the dispersion effect due to steric hindrance. In addition, if the polyester end is a cyclic unit, the dispersion effect due to steric hindrance can be further improved. Examples of the cyclic unit at the polyester end include caprolactone.

[0055] Examples of polyamine-based polymer dispersants having a polyester structure in the side chain include Lubrizol's Solsperse 13240 and 24000. Also included is Ajisper PB821 manufactured by Ajinomoto Fine-Techno.

[0056] The content of (D) is preferably 1.5 or more and 3.0 or less in mass ratio to (B). When the content is 3.0 or less, it is easy to secure a portion to which (C) can adhere on the surface of the (B) carbon black, and it is easy to secure the dispersion effect of (B) by (C). This makes it easy to secure the combined effect of (C) and (D). From this viewpoint, the content is more preferably 2.5 or less. On the other hand, when the content is 1.5 or more, it is possible to increase the dispersion effect of (B) due to the steric hindrance of (D). From this viewpoint, the content is more preferably 2.0 or more.

[0057] As for the quantitative ratio of (C) to (D), from the viewpoint of easily achieving both the dispersion effect of (C) on (B) and the dispersion effect of (D) on (B), the content of (D) relative to (C) is preferably 0.6 or more and 1.5 or less in mass ratio.

[0058] The surface layer 16 may contain roughness-forming particles. The roughness-forming particles are particles for imparting roughness to the surface of the surface layer 16. In other words, the particles are particles for imparting unevenness to the surface of the surface layer 16. The surface unevenness of the surface layer 16 increases the discharge space between the photoreceptor and the charging roll 10, promoting discharge. This improves charging properties and suppresses image defects such as horizontal streaks and unevenness.

[0059] The roughness-forming particles are made of resin particles or the like. The material of the roughness-forming particles is not particularly limited. The roughness-forming particles are preferably made of a polymer having a carbonyl group or a polymer having a hydroxyl group. This is because the polymer having a carbonyl group or the polymer having a hydroxyl group is a material with a relatively high dielectric constant, and the charging roll 10 can easily ensure excellent charging properties. Examples of the polymer having a carbonyl group include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, silicone graft acrylic polymer, acrylic graft silicone polymer, and urethane rubber. Examples of the polymer having a hydroxyl group include epoxy resin.

[0060] The size of the roughness-forming particles is not particularly limited, but from the viewpoint of easily ensuring uniform charging properties, the average particle diameter is preferably 3.0 μm or more and 50 μm or less. More preferably, the average particle diameter is 5.0 μm or more and 30 μm or less. The average particle diameter of the roughness-forming particles is expressed as the average of any 20 points when the surface of the surface layer 16 is observed with a laser microscope, and the diameter of the roughness-forming particles visible during surface observation is taken as the particle diameter.

[0061] The content of the roughness-forming particles in the surface layer 16 is not particularly limited, but from the viewpoint of easily ensuring uniform electrostatic charge, it is preferably 3 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the binder polymer (A) in the surface layer 16. It is more preferably 5 parts by mass or more and 30 parts by mass or less.

[0062] The volume resistivity of the surface layer 16 is preferably set to a semiconductive region from the viewpoint of electrostatic chargeability. 7 ~1.0×10 10 The volume resistivity may be set in the range of Ω·cm. The volume resistivity may be measured in accordance with JIS K6911. The thickness of the surface layer 16 is not particularly limited, and may be set in the range of 0.1 to 3.0 μm. The thickness of the surface layer 16 may be measured by observing the cross section using a laser microscope (such as Keyence's "VK-9510"). For example, the distance from the surface of the elastic layer 14 to the surface of the surface layer 16 may be measured at five arbitrary positions, and the thickness may be expressed as the average.

[0063] The charging roll 10 can be produced by forming an elastic layer 14 on the outer peripheral surface of a shaft body, and then forming a surface layer 16 on the outer peripheral surface of the elastic layer 14 .

[0064] The elastic layer 14 can be formed, for example, as follows: First, a shaft is coaxially placed in the hollow portion of a roll molding die, and an uncrosslinked composition for forming an elastic layer is injected and heated and cured (crosslinked), and then the composition is demolded, or the uncrosslinked composition for forming an elastic layer is extruded onto the surface of the shaft to form the elastic layer 14 on the outer periphery of the shaft.

[0065] To form the surface layer 16, a surface layer composition is used. The surface layer composition includes the above-mentioned (A) to (D). The surface layer composition can be formed by mixing (B) and (D), then mixing (C), and then mixing (A). By mixing (D) with (B) before (C), (C) and (D) can be appropriately adsorbed to (B). If (C) is mixed with (B) before (D), (D) is less likely to be adsorbed to (B), and the dispersion effect of (B) by (D) is less likely to be obtained.

[0066] The surface layer composition may appropriately contain a solvent such as an organic solvent such as methyl ethyl ketone, toluene, acetone, ethyl acetate, butyl acetate, methyl isobutyl ketone (MIBK), THF, or DMF, or a water-soluble solvent such as methanol or ethanol, in order to adjust the viscosity.

[0067] The surface layer 16 can be formed by a method such as coating a surface layer composition onto the outer peripheral surface of the elastic layer 14. As the coating method, various coating methods such as roll coating, dipping, spray coating, etc. The coated surface layer 16 may be irradiated with ultraviolet light or heat treated as necessary.

[0068] According to the charging roll 10 having the above configuration, the use of two types of dispersants (C) and (D) in combination as a dispersant for the carbon black (B) in the surface layer 16 enables the carbon black to be well dispersed even in binders such as fluoropolymers and silicone polymers in which carbon black is difficult to disperse. Furthermore, due to the charging effect of the carbon black and the dispersing effect of that carbon black, the charging roll 10 has excellent charging properties and uniform charging properties. EXAMPLES

[0069] The present invention will be described in detail below using examples and comparative examples.

[0070] Example 1 <Preparation of Conductive Rubber Composition> A conductive rubber composition was prepared by compounding 100 parts by mass of isoprene rubber with 30 parts by mass of carbon black, 6 parts by mass of zinc oxide, 2 parts by mass of stearic acid, 1 part by mass of sulfur, 0.5 parts by mass of thiazole-based vulcanization accelerator, 0.5 parts by mass of thiuranium-based vulcanization accelerator, and 50 parts by mass of heavy calcium carbonate, and kneading the mixture for 10 minutes using an internal mixer adjusted to a temperature of 50°C.

[0071] As materials for the conductive rubber composition, the following materials were prepared. Isoprene rubber (IR): JSR "JSR IR2200" Carbon black: Cabot Japan "Show Black N762" Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Stearic acid: "Sakura Stearic Acid" made by Nippon Oil & Fats Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Thiazole-based vulcanization accelerator: "Noccela DM" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. - Thiuram-based vulcanization accelerator: "Noccela TRA" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Heavy calcium carbonate: Shiraishi Calcium's "Whiten B", average particle size 3.6μm

[0072] <Preparation of Elastic Layer> A core wire (diameter 8 mm) was set in a molding die (pipe-shaped), the above composition was injected, and the die was heated at 180°C for 30 minutes. The die was then cooled and demolded to form an elastomer layer made of a conductive rubber elastomer having a thickness of 1.9 mm around the outer periphery of the core wire.

[0073] <Preparation of surface layer> In the compounding composition (parts by mass) shown in Table 1, carbon black <b-1>Dispersants with aromatic rings <d-1>Then, a dispersant having a carboxyl group is added. <c-1>Then, the binder is mixed. <a-1>and roughness forming particles <1> The above were mixed, 200 parts by mass of methyl ethyl ketone (MEK) was added, and the mixture was stirred at a predetermined stirring speed to prepare a surface layer composition. Next, while continuing to stir, the surface layer composition was roll-coated on the outer peripheral surface of the elastic layer, and a heat treatment was performed to form a surface layer having a thickness of 1.0 μm on the outer periphery of the elastic layer. In this way, the charging roll of Example 1 was produced.

[0074] (Examples 2 to 11, Comparative Examples 1 to 4) A charging roll was produced in the same manner as in Example 1, except that the surface layer composition had the composition shown in Table 1.

[0075] The following materials were prepared as the surface layer composition. (binder) A-1: Silicone polymer (dielectric constant 2.2), "SLK" manufactured by Shin-Etsu Chemical Co., Ltd. A-2: Fluoropolymer (dielectric constant 2.5), Daikin's "Neoflon PCTFE" X-1: Fluorine polymer (dielectric constant 2.1), Daikin's "Neoflon PFA" X-2: Fluoropolymer (dielectric constant 2.6), Daikin's "Neoflon ETFE" (Carbon Black) B-1 (DBP absorption capacity 124ml / 100g, BET specific surface area 43m 2 / g, average particle size 41 nm): Asahi Carbon "Asahi #60H (N-568)" B-2 (DBP absorption capacity 160ml / 100g, BET specific surface area 75m 2 / g, average particle size 35 nm): Denka "Denka Black" B-3 (DBP absorption capacity 115ml / 100g, BET specific surface area 42m 2 / g, average particle size 44nm): Tokai Carbon "Seasto SO" B-4 (DBP absorption capacity 155ml / 100g, BET specific surface area 25m 2 / g, average particle size 75nm): Tokai Carbon "Seat GFY" B-5 (DBP absorption capacity 125ml / 100g, BET specific surface area 126m 2 / g, average particle size 25nm): Tokai Carbon "Seasto 7HM" Y-1 (DBP absorption capacity 175ml / 100g, BET specific surface area 165m 2 / g, average particle size 20nm): Mitsubishi Chemical “#3400B” Y-2 (DBP absorption capacity 58ml / 100g, BET specific surface area 180m 2 / g, average particle size 18 nm): Mitsubishi Chemical “#1000” Y-3 (DBP absorption capacity 360ml / 100g, BET specific surface area 800m 2 / g, average particle size 32 nm): Ketjen EC300J manufactured by Ketjen Black International (Dispersant) C-1: Ester-type polyurethane polymer dispersant with carboxyl groups, Lubrizol's Solsperse 75500 C-2: Polyethyleneimine-based polymer dispersant with carboxyl groups, Lubrizol's Solsperse 32500 D-1: Polyamine polymer dispersant with polyester structure in the side chain, Lubrizol's Solsperse 24000 D-2: Polyethyleneimine-based polymer dispersant with polyester structure in the side chain, Ajinomoto Fine Techno's "Ajisper PB821" Z-1: Ester-type polyurethane polymer dispersant without carboxyl group, Lubrizol's Solsperse 32600 Z-2: Polyamine polymer dispersant that does not have a polyester structure in the side chain, "Disparlon DA-234" manufactured by Kusumoto Chemicals (Grains for roughness formation) PMMA: Chemisnow MX3000 manufactured by Soken Chemical, average particle size 30μm Epoxy: Toray "Trepearl EP", average particle size 30μm Urethane: Negami Industrial Co., Ltd. "Art Pearl C200", average particle size 30μm

[0076] The produced charging roll was subjected to the following image evaluation.

[0077] (White dots: Evaluation of carbon black dispersibility) The produced charging roll was attached to the unit (black) of an actual machine (RICOH "MP C6004"), and images were output at 25% density halftone in a 10℃ x 10% RH environment, and an evaluation was performed after 500,000 sheets were printed. Images with no white spots were rated as particularly good (◎), images with white spots found in the image but within the acceptable range were rated as good (◯), and images with white spots found in the image but outside the acceptable range were rated as poor (×).

[0078] (Black dots: Evaluation of dispersibility of dispersant C) The produced charging roll was attached to the unit (black) of an actual machine (RICOH "MP C6004"), and images were output at 25% density halftone in a 10℃ x 10% RH environment, and an evaluation was performed after 500,000 sheets were printed. Images with no black spots were rated as particularly good (◎), images with black spots found in the image but within the acceptable range were rated as good (◯), and images with black spots found in the image but outside the acceptable range were rated as poor (×).

[0079] (Fog: Low dielectric constant) The produced charging roll was attached to the unit (black) of an actual machine (RICOH "MP C6004"), and images were output at 25% density halftone in a 10℃ x 10% RH environment, and an evaluation was performed after 500,000 sheets were printed. Images with no fog were rated as particularly good (◎), images with fog found in the image but within the acceptable range were rated as good (◯), and images with fog found in the image but outside the acceptable range were rated as poor (×).

[0080] (White stripes: high dielectric constant) The produced charging roll was attached to the unit (black) of an actual machine (RICOH "MP C6004"), and images were output at 25% density halftone in an environment of 35°C x 80% RH, and an evaluation was performed after 500,000 sheets were printed. Images with no white streaks were rated as particularly good (◎), images with white streaks found in the image but within the acceptable range were rated as good (◯), and images with white streaks found in the image but outside the acceptable range were rated as poor (×).

[0081] [Table 1]

[0082] In Comparative Example 1, the relative dielectric constant of the binder polymer of the surface layer is too low, so the electrostatic capacitance is small and the charging property is poor, resulting in fogging. In Comparative Example 2, the relative dielectric constant of the binder polymer of the surface layer is too high, so the compatibility between the binder polymer and the dispersant C is too high, so the dispersing effect of the carbon black is reduced, and white spots outside the allowable range are generated. In addition, the charging property is highly dependent on the environment, and white streaks are generated in a high temperature and high humidity environment (LL environment). In Comparative Example 3, in a specified binder polymer, a polyethyleneimine-based polymer dispersant D having a polyester structure in the side chain is blended with carbon black, but a dispersant C having a carboxyl group is not blended. Therefore, the dispersibility of carbon black is poor, and white spots outside the allowable range are generated. In Comparative Example 4, in a specified binder polymer, a dispersant C having a carboxyl group is blended with carbon black, but a polyethyleneimine-based polymer dispersant D having a polyester structure in the side chain is not blended. Therefore, the dispersibility of carbon black is poor, and white spots outside the allowable range are generated.

[0083] On the other hand, in the Examples, the surface layer contains (A) one or more polymers selected from fluoropolymers and silicone polymers having a dielectric constant of 2.2 or more and 2.5 or less, (B) carbon black, (C) one or more polymer dispersants selected from ester-type polyurethane-based polymer dispersants and polyethyleneimine-based polymer dispersants having a carboxyl group, and (D) a polyamine-based polymer dispersant having a polyester structure in the side chain, and therefore it is understood that the Examples have excellent dispersibility of carbon black and excellent uniform charging properties and charging properties.

[0084] Comparison between Examples (Examples 1-2 and Examples 4-6) shows that when the DBP absorption amount, specific surface area, and average particle size of carbon black are within the specified ranges, no fog is observed on the image, the resistance is low, the capacitance is high, and the charging properties are excellent. Comparison between Examples (Examples 1-3 and Examples 7-8) shows that when the content of (C) relative to (B) is within the specified ranges, no black spots are observed on the image, and the charging properties are excellent. It is also shown that no white spots are observed on the image, and the charging properties are excellent. Comparison between Examples (Examples 1-3 and Examples 9-10) shows that when the content of (D) relative to (B) is within the specified ranges, no white spots are observed on the image, and the charging properties are excellent.

[0085] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0086] 10. Charging roll 12 Axial body 14 Elastic layer 16 Surface layer

Claims

1. The shaft body includes an elastic layer formed on an outer peripheral surface of the shaft body, and a surface layer formed on the outer peripheral surface of the elastic layer, The charging roll for electrophotographic equipment, wherein the surface layer contains the following (A) to (D): (A) one or more polymers selected from fluoropolymers and silicone polymers, each having a dielectric constant of 2.2 or more and 2.5 or less; (B) Carbon black (C) one or more polymer dispersants having a carboxyl group selected from ester-type polyurethane polymer dispersants and polyethyleneimine polymer dispersants (D) Polyamine-based polymer dispersant having a polyester structure in the side chain

2. The DBP absorption of (B) is 115 cm 3 / 100g or more 160cm 3 / 100g or less, and the specific surface area of ​​(B) is 25 m 2 / g or more 75m 2 2. The charging roll for electrophotographic equipment according to claim 1, wherein the average particle size of said (B) is 35 nm or more and 75 nm or less.

3. 3. The charging roll for an electrophotographic device according to claim 1, wherein the surface layer contains roughness-forming particles that form surface roughness, and the roughness-forming particles have either or both of a carbonyl group and a hydroxyl group.

4. 4. The charging roll for electrophotographic equipment according to claim 1, wherein the content of said (D) relative to said (B) is 1.5 or more and 3.0 or less in mass ratio.

5. 5. The charging roll for an electrophotographic device according to claim 1, wherein the content of said (C) relative to said (B) is 1.5 or more and 3.0 or less in mass ratio.

6. 6. The charging roll for an electrophotographic device according to claim 1, wherein the polyester (D) has a terminal end that is cyclic.

7. 7. The charging roll for an electrophotographic apparatus according to claim 1, wherein the (C) has a polyalkylene oxide structure in its main chain.

8. 8. The charging roll for an electrophotographic apparatus according to claim 1, wherein the carboxyl group of (C) is a carboxylate salt group having a quaternary amine structure.

9. A method for producing a charging roll for an electrophotographic device according to any one of claims 1 to 8, comprising the steps of: the surface layer is formed of a surface layer composition containing the components (A) to (D), the surface layer composition is formed by mixing (B) and (D), then mixing (C), and then mixing (A).

Citation Information

Patent Citations

  • Charging element for electrostatic charging and method for its manufacture

    DE102012208453A1

  • Developer carrier and its production

    JP1992037878A

  • Conductive roller

    JP1994040959U

  • Roller and device for developing

    JP1997269652A

  • Electrically semiconductive roll

    JP1998268613A